Trends and Barriers of Medication Treatment for Opioid Use Disorders: A Systematic Review and Meta-Analysis - Hutchison, Morica (Journal of drug issues, 2025)
Adherence to and retention in Medication Treatment for Opioid Use Disorders (MOUD) persist. We systematically reviewed trends of USA MOUD adherence, retention, and barriers from 2011–2021. Primary outcomes were adherence to and retention in MOUD, abstinence, adverse events, and treatment barriers. Effects of inverse variance random meta-analyses were examined using proportions and 95% CIs. 28 studies (102,318 patients), 78.1% male. Adherence was 56% across all studies, highest for methadone (73%). Retention by study design was heterogeneous: case series (57%), cohorts (47%), and RCTs (70%). The most common barriers were younger age, comorbid diagnoses, daily attendance, no insurance, and transportation. Abstinence was 72%, and adverse events was 5%. There was high heterogeneity in MOUD across drug types and study designs. Our findings extend the knowledge base of MOUD treatment to describe barriers that underpin the focus on retention in care above adherence given its focus to harm reduction principles.